International agrarian conflict on palm oil plantations in Indonesia - Ali, Agustin (Journal of Law Science, 2025)
International agricultural disputes between foreign plantation businesses and indigenous Indonesians demonstrate the intricate relationship between customary, national, and international civil law. Customary law is acknowledged in Indonesian law, although formal legality that favors foreign investment hinders its application, often resulting in indigenous peoples losing access to customary land crucial to their economic and cultural well-being. This paper examines how international civil law affects multinational plantation firms' agricultural conflicts and their obligation to indigenous peoples. The research employs a normative and comprehensive-juridical approach, analyzing national rules, international legal documents like the UN Declaration on the Rights of Indigenous Peoples (UNDRIP), and case studies. The findings reveal that the conflict between customary, national, and international civil law is the most significant barrier to resolving these disputes. Foreign firms often advocate for international arbitration, which undermines local and indigenous mechanisms. The absence of harmonization between customary practices, national legal frameworks, and international standards further complicates determining the applicable law. Additionally, while international corporate responsibility norms like the UN Guiding Principles on Business and Human Rights exist, foreign companies frequently disregard their social obligations to indigenous communities. The study contributes to the field by emphasizing the need for harmonized legal frameworks and proposing practical solutions, including strengthening the recognition and enforcement of customary law, implementing Free, Prior, and Informed Consent (FPIC) mechanisms, and embedding international principles into national policies. These measures aim to achieve equitable resolutions by balancing economic development with indigenous rights and environmental sustainability, offering a model for resolving cross-border agrarian disputes in similar contexts.